An improved time discretized non-linear velocity obstacle method for multi-ship encounter detection. (15th January 2020) - Chen, Pengfei; Huang, Yamin; Papadimitriou, Eleonora; Mou, Junmin; van Gelder, P.H.A.J.M.
Abstract: Ship collision is one of the major contributors of maritime accidents. Quantitative risk analysis of such accidents is an effective tool for maritime safety administrations to understand the current risk level and propose risk mitigation measures. In this paper, an improved Time Discretized Non-linear Velocity obstacle (TD-NLVO) algorithm is proposed to detect multiple ship encounter situations using historical AIS data. Boolean operation on the individual NLVO is integrated with TD-NLVO using the union of the velocity-obstacle sets to determine a dangerous encounter situation according to the pre-set criteria. Two case studies are implemented to illustrate the capability of the proposed algorithm. A comparison is conducted between the previous and the improved methods. The results indicate that the improved method can effectively identify a multiple ship encounter which satisfies the pre-set criteria. The improved method has the potential to provide more detailed information for stakeholders e.g. maritime safety administration, etc. to propose risk mitigation measures as well as to improve the accuracy of geometric probability analysis for ship collision risk. Highlights: New approach for multiple ship encounter analysis using Non-Linear Velocity obstacle and AIS data. Individual VOs are combined the construct the velocity obstacles for multi-ship encounter. TD-NLVO is introduced to build individual velocity obstacle set induced by each target ship.